The effectiveness of ceramide moisturizing cream in pruritic papular eruption treatment of HIV/AIDS patients - Sayekti, Ayu Wikan; Putri, Ann Kautsarina; Pudjiati, Satiti Retno; Winarni, Dwi Retno Adi (Explorer Front, 2024)
Background: Pruritic papular eruption (PPE) is one of the most common skin manifestations in HIV/AIDS patients. Pruritic papular eruptions are due to immune dysregulation, causing dominance of interleukin-4, which causes a decrease in ceramide synthesis (CER) and impaired skin barrier function. This study aimed to investigate the effectiveness of CER over non-CER moisturizing cream in HIV/AIDS patients with PPE. Methods: Double-blind experimental design. The research subjects are PPE patients at Dr. Sardjito General Hospital. CER and non-CER moisturizing cream are applied for three weeks, respectively. Analysis of the trans-epidermal water loss (TEWL), skin hydration, and itching were analyzed using an unpaired T-test or the Mann-Whitney test with a significance of p<0.05. Results: Ceramide synthesis moisturizing cream decreased the TEWL value by 3.56 ± 2.38 g/m2/hour; increased the value of skin hydration by 16.39±7.19 a.u.; decreased skin lesions by 0.79 ± 4.95; reduced itching by 1.54 ± 0.78 and without causing side effects. Non-CER moisturizing cream decreased the TEWL value by 1.57 ± 2.00 g/m2/hour; increased the value of skin hydration by 12.03 ± 6.88 a.u.; decreased skin lesions by 1.42 ± 3.00; reduced itching by 1.17 ± 0.70 and also without causing side effects. Conclusion: Ceramide cream is more effective than non-CER moisturizing cream in reducing TEWL and increasing skin hydration. Ceramide and non-CER moisturizing creams have the same effectiveness in reducing the number of lesions and reducing itching. Ceramide and non-CER moisturizing creams do not cause side effects.